Unravelling myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS): Gender‐specific changes in the microRNA expression profiling in ME/CFS. Issue 10 (14th April 2020) - Cheema, Amanpreet K.; Sarria, Leonor; Bekheit, Mina; Collado, Fanny; Almenar‐Pérez, Eloy; Martín‐Martínez, Eva; Alegre, Jose; Castro‐Marrero, Jesus; Fletcher, Mary A.; Klimas, Nancy G.; Oltra, Elisa; Nathanson, Lubov
Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a multisystem illness characterized by medically unexplained debilitating fatigue with suggested altered immunological state. Our study aimed to explore peripheral blood mononuclear cells (PBMCs) for microRNAs (miRNAs) expression in ME/CFS subjects under an exercise challenge. The findings highlight the immune response and inflammation links to differential miRNA expression in ME/CFS. The present study is particularly important in being the first to uncover the differences that exist in miRNA expression patterns in males and females with ME/CFS in response to exercise. This provides new evidence for the understanding of differential miRNA expression patterns and post‐exertional malaise in ME/CFS. We also report miRNA expression pattern differences associating with the nutritional status in individuals with ME/CFS, highlighting the effect of subjects' metabolic state on molecular changes to be considered in clinical research within the NINDS/CDC ME/CFS Common Data Elements. The identification of gender‐based miRNAs importantly provides new insights into gender‐specific ME/CFS susceptibility and demands exploration of sex‐suited ME/CFS therapeutics.